The role of local channels (UTV) erbil and (UTV) dohuk to guide audiences in the Iraqi Kurdistan region (2004 – 2009) - Ayoub Hussien Abdullah,; Siti Rugayah Hj. Tibek, (Institut Kajian Rantau Asia Barat, 2011)
The Islamic media have been playing a prominent role in the Kurdish people's awareness in the Iraq Kurdistan Region in various facets of life. On the assumption that Media are a real power which are able to steer the nation toward different behaviors, the researcher will study the reality of the Islamic Media in Kurdistan Region of Iraq through exploring two models of Islamic media in the region. According to the questionnaire conducted by the Nongovernmental Iraq Civil Society Program Organization (ICSP) from 10th of March to 10th of April 2007, the Islamic visual media had the priority of the most influential media institutions in Kurdistan Region; As a result, that promotes the researcher to carry out an empirical study- a questionnaire in which viewers give their views to indicate the role of the Islamic media in enlightenment viewers- of two samples of the Islamic visual media; (UTV) Dohuk local channel, and (UTV) Erbil local channel respectively ,using comprehensive questions to nine themes concluded with a correlation matrix. The research has proved the existence of dozens of various Islamic media institutions in the region, including institutions that are specialized in concentrating on a specific aspect of life or a specific class of society. The research recommends that these institutions be provided with advanced media equipment,necessary supplies and adequate funds so that they will be able to communicate their message perfectly.